vB_PaeM_MIJ3, a Novel Jumbo Phage Infecting Pseudomonas aeruginosa, Possesses Unusual Genomic Features - Imam, Mohammed; Alrashid, Bandar; Patel, Faizal; Dowah, Ahmed S. A.; Brown, Nathan; Millard, Andrew; Clokie, Martha R. J.; Galyov, Edouard E. (Frontiers in Microbiology, 2019)
Phages are the most abundant biological entity on Earth. There are many variants in phage virion sizes, morphology and genome sizes. Large virion sized phages, with genome sizes greater than 200 kbp have been identified and termed as Jumbo phages. These phages exhibit certain characteristics that have not been reported in phages with smaller genomes. In this work, a jumbo phage named MIJ3 (vB_PaeM_MIJ3) that infects Pseudomonas aeruginosa PAO1, was isolated from an equine livery yard in Leicestershire, United Kingdom. The genome and biological characteristics of this phage have been investigated. MIJ3 is a Myovirus with multiple long tail fibres. The host range of MIJ3 revealed that it has the ability to infect many clinical isolates of P. aeruginosa. Bioinformatics analysis of the phage genome indicated that MIJ3 is closely related to the Pseudomonas phage, PA5oct. Both phages belong to the same species but PA5oct has not been formally identified. MIJ3 possesses several unusual features that are either rarely present in other phages or have not yet been reported. In particular, MIJ3 encodes a FtsH-like protein, and a putative lysidine synthase, TilS. These two proteins have not been reported in phages. MIJ3 also possesses a split DNA polymerase B with a novel intein. Of particular interest, unlike other jumbo phages infecting Pseudomonas spp., MIJ3 lacks the genetic elements required for the formation of the phage nucleus, which was believed to be conserved across jumbo Pseudomonas phages.